Pengaruh Harga, Citra Merek, Kualitas, dan Promosi terhadap Keputusan Pembelian Produk Nugget di Malang - Loe, A; Murti, A; Suroto, K S (PETERPAN (Jurnal Peternakan Terapan), 2025)
The rise in processed meat product consumption in Malang City during 2021–2023 had an impact on this study. In 2021, 0.104 kg/person/year, 0.624%/person/year, and 0.988%/person/year were the consumption levels of processed items. Finding out how So Good chicken nuggets' brand image, pricing, advertising, and product quality affected consumers' decisions to buy was the goal. Numerical data collection is the main goal of this study's quantitative methodology. The study, which had 900 participants, was carried out in Malang City, East Java. Accidental sampling, which depends on the data that is available, was the sample collection approach that was employed. 100  individuals were included in this study using the Slovin formula. The study's findings regarding product quality, pricing,promotion, and brand.